2022
DOI: 10.3390/biom12020286
|View full text |Cite
|
Sign up to set email alerts
|

Mcm5 Represses Endodermal Migration through Cxcr4a-itgb1b Cascade Instead of Cell Cycle Control

Abstract: Minichromosome maintenance protein 5 (MCM5) is a critical cell cycle regulator; its role in DNA replication is well known, but whether it is involved in the regulation of organogenesis in a cell cycle-independent way, is far from clear. In this study, we found that a loss of mcm5 function resulted in a mildly smaller liver, but that mcm5 overexpression led to liver bifida. Further, the data showed that mcm5 overexpression delayed endodermal migration in the ventral–dorsal axis and induced the liver bifida. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…One color in situ hybridization was performed as described in a previous study (Liu et al, 2019). The previous probes fabp10, prox1, hhex, and fabp2 were used as described in previous reports (Zhang et al, 2022). The CDs of amd1 and skp2 were amplified using PCR and cloned into the vector pcs2 + , then linearized the plasmids and synthesized the individual antisense probe as previously reported (Zhang et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One color in situ hybridization was performed as described in a previous study (Liu et al, 2019). The previous probes fabp10, prox1, hhex, and fabp2 were used as described in previous reports (Zhang et al, 2022). The CDs of amd1 and skp2 were amplified using PCR and cloned into the vector pcs2 + , then linearized the plasmids and synthesized the individual antisense probe as previously reported (Zhang et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The previous probes fabp10, prox1, hhex, and fabp2 were used as described in previous reports (Zhang et al, 2022). The CDs of amd1 and skp2 were amplified using PCR and cloned into the vector pcs2 + , then linearized the plasmids and synthesized the individual antisense probe as previously reported (Zhang et al, 2022). Two color in situ hybridization was performed as described in a previous study (Dunn et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Microchromosome maintenance protein 5 (MCM5) is a key cell cycle regulator located on chromosome 22Q13.1 [ 12 ], whose role in DNA replication is verified [ 13 ]. MCM5 is a DNA licensing factor as an ingredient of the MCM2-7 complex, a putative replicative helicase vital for the initiation and extension of "once per cell cycle" DNA replication in eukaryotic cells [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCM5 is a member of the crucial component of DNA replication licensing system and MCM5 loss leads to DNA duplication defects 28 . Previous work demonstrated that the number of MCM5 is excess over that of replication origins 29 and the excess MCM5 plays a critical role in regulation of gene transcription during embryonic development 30 . Here, we identi ed that, mcm5 loss disturbed DNA duplication of immature T lymphocyte and sequentially led to up-regulation of p53 signaling, which resulting in immature T lymphocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%